The role of corporate governance in enhancing the influence of tax planning on tax disclosure - Syafi’i, M; Chandrarin, Grahita; Zuhroh, Diana (Management and Entrepreneurship: Trends of Development, 2023)
Purpose: The paper studies the relationship between tax disclosure, tax planning and governance in the context of Indonesian public companies. It examines the impact of opportunistic management behavior on tax disclosure and the role of governance in influencing tax-related management decisions. Design/Methodology/Approach: The study uses Moderated Regression Analysis (MRA) to test the relationship between the variables. For carrying out the analysis, the secondary data recorded on the Indonesian Stock Exchange for the period 2017-2021 is used. This study includes all companies listed on the IDX, totaling 787 across various industrial sectors. However, only 74 companies meet the criteria. Findings: The results suggest that tax planning can be used as a means to maintain corporate prosperity, but it may weaken tax disclosure. Governance plays an important role in influencing management decisions regarding tax management. Originality/value: The study provides insights into the dynamics of tax disclosure, tax planning, and governance in the Indonesian context. JEL Classification: G30, G31, G32